Vena femoral bitroncular con tronco axiofemoral originado de la vena safena parva (2014)
Knowledge of the anatomy of the veins of the lower limbs is fundamental to understanding the pathophysiology, diagnosis and treatment of vascular diseases. Most errors in the diagnosis and treatment of these diseases is due to anatomical variations thereof. This study analyzes and anatomical variation found in a female body, in which a duplication of the popliteal vein, vein one passing through the adductor hiatus evidenced discussed, while the other ascends the face posterior of the thigh along the path of the sciatic nerve. While the veins of the lower limbs stored common characteristics, each time is described in greater detail a large number of variations which influences thrombus search items described in refereed journals and are not taken into account other patterns distribution.